2010
DOI: 10.1021/es100915j
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Alkylphenolic Compounds during Activated Sludge Treatment: Impact of Loading and Organic Composition

Abstract: The impact of loading and organic composition on the fate of alkylphenolic compounds in the activated sludge plant (ASP) has been studied. Three ASP designs comprising carbonaceous, carbonaceous/nitrification, and carbonaceous/nitrification/denitrification treatment were examined to demonstrate the impact of increasing levels of process complexity and to incorporate a spectrum of loading conditions. Based on mass balance, overall biodegradation efficiencies for nonylphenol ethoxylates (NPEOs), short chain carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 29 publications
(71 reference statements)
0
16
0
Order By: Relevance
“…In order to compare the pharmaceutical and endocrine removal efficiencies observed in the simplified treatment systems studied here with those shown by the activated sludge (AS) systems, data gathered from different studies and research groups (Carballa et al, 2004;Clara et al, 2005aClara et al, , 2005bJoss et al, 2005;Vieno et al, 2005;Batt et al, 2006;Bernhard et al, 2006;Lishman et al, 2006;Nakada et al, 2006;Göbel et al, 2007;Radjenovic et al, 2007;Tan et al, 2007;Gulkowska et al, 2008;Pothitou and Voutsa, 2008;Ying et al, 2008;Janex-Habib et al, 2009;Kasprzyk-Hordern et al, 2009;Radjenovic et al, 2009;Choubert et al, 2011;Jelic et al, 2011;McAdam et al, 2011;Pedrouzo et al, 2011;Zhang et al, 2011) was compiled and presented in Fig. 5.…”
Section: Micropollutant Removal In Simplified Wwtpsmentioning
confidence: 99%
“…In order to compare the pharmaceutical and endocrine removal efficiencies observed in the simplified treatment systems studied here with those shown by the activated sludge (AS) systems, data gathered from different studies and research groups (Carballa et al, 2004;Clara et al, 2005aClara et al, , 2005bJoss et al, 2005;Vieno et al, 2005;Batt et al, 2006;Bernhard et al, 2006;Lishman et al, 2006;Nakada et al, 2006;Göbel et al, 2007;Radjenovic et al, 2007;Tan et al, 2007;Gulkowska et al, 2008;Pothitou and Voutsa, 2008;Ying et al, 2008;Janex-Habib et al, 2009;Kasprzyk-Hordern et al, 2009;Radjenovic et al, 2009;Choubert et al, 2011;Jelic et al, 2011;McAdam et al, 2011;Pedrouzo et al, 2011;Zhang et al, 2011) was compiled and presented in Fig. 5.…”
Section: Micropollutant Removal In Simplified Wwtpsmentioning
confidence: 99%
“…In addition these digesters had the lowest percentage removal of E3 observed (Table 2) where only 17% or 4% was removed in comparison to>43% at mesophilic conditions which implies that E1 had also been converted to E3. possibly due to some operational alterations at the works affecting the solids and/or hydraulic retention times or food to micro-organism ratio in the activated sludge plant which can effect NPEO breakdown [38].…”
Section: Effect Of Retention Time On the Removal Of Steroid Estrogensmentioning
confidence: 99%
“…In a strong agreement, Vader et al [130] suggested that high removal of estrogens (in the range of 79-95%) was mainly attributed to the nitrifying stage. Findings of McAdam et al [131] also showed the same patterns where nitrifying appeared in higher de-ethoxylation of long-chain nonylphenolic compounds (NP [5][6][7][8][9][10][11][12] EO), at approximately 92%, and partial removal of NP, whereas non-nitrifying process yielded poorer de-ethoxylation and an accumulation of NP.…”
Section: The Role Of the Secondary Activated Sludge Processmentioning
confidence: 74%